Substoichiometric Radiochemical Determination of Selenium by Sodium-isopropyl Xanthate as a Reagent - Muralikrishna, K.V.; Polaiah, B.; Rangamannar, B. (Asian Journal of Chemistry, 2010)
A simple selective and sensitive method for the determination of selenium has been investigated. Sodium isopropyl xanthate was used as are agent and chloroform as an extractant. The complex was extracted into chloroform from pH 4 acetate buffer. The influence of various interferencesions on the extraction was studied. 3—10 μg selenium was detenninted with a precision of 1.42%. The method developed was utilized to determine the selenium content in Jaggery and wheat samples.